Ag-Cu electrode-based conductive bridge random access memory device and preparation method thereof

By using Ag-Cu alloy electrodes to optimize the conductive filament structure of CBRAM devices, the consistency and stability problems of traditional CBRAM devices are solved, low-power and high-storage-density non-volatile memory devices are realized, and the development of a new generation of low-power non-volatile memory devices is promoted.

CN120603481APending Publication Date: 2025-09-05HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510900142.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

Traditional pure metal electrode-based CBRAM devices have problems such as high forming voltage, inconsistent set/reset transition voltage, poor stability, and a small ratio of high and low resistance states, making it difficult to meet the requirements of high storage density, low power consumption, and high read and write speeds.

Method used

Ag-Cu alloy electrodes are used to replace traditional pure metal electrodes. Ag-Cu alloy electrodes and resistive switching layers are prepared by magnetron sputtering to optimize the microstructure of the conductive filaments, reduce the randomness of the conductive filament growth, and improve the consistency and stability of the device.

Benefits of technology

The forming voltage and set/reset transition voltage are significantly reduced, the consistency of high and low resistance states and transition voltages is enhanced, the operating power consumption is reduced, and low power consumption and high consistency are maintained in 100 read and write cycle tests, thereby increasing the storage window size.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120603481A_ABST
    Figure CN120603481A_ABST
Patent Text Reader

Abstract

The invention provides an Ag-Cu electrode-based conductive bridge random access memory device and a preparation method thereof. According to the Ag-Cu electrode-based conductive bridge random access memory device, the Ag-Cu alloy electrodes are used for replacing traditional pure metal electrodes, the performance of the device is remarkably improved, the proportion of high and low resistance values is increased, the Forming voltage and the set / reset conversion voltage are remarkably reduced, and the consistency and stability of the high and low resistance states and the set / reset conversion voltage are enhanced. The principle is that the microstructure of the conductive wire in the device is optimized, and the randomness of the growth of the conductive wire is reduced, so that the consistency and the stability of the CBRAM device are optimized, and the working power consumption is effectively reduced. According to the invention, the development and large-scale commercialization of a new-generation low-power-consumption nonvolatile memory device are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microelectronic integrated circuits, and in particular to an Ag-Cu electrode-based conductive bridge random access memory device (CBRAM) and a preparation method thereof. Background Art

[0002] In recent years, with the continuous advancement of the big data era, consumer electronics such as mobile phones and laptops, as well as technologies such as edge computing, artificial intelligence, and machine learning, have rapidly developed, leading to an exponential increase in the global volume of data. Market demand for non-volatile memory with high storage density, low power consumption, and high read / write speeds continues to rise. In this context, modern technological applications are placing increasing demands on memory performance. Currently, the primary technology for non-volatile memory devices is Flash. However, Flash faces physical limitations as nanoscale scaling progresses towards high integration. It also suffers from issues such as high overall power consumption and slow read / write speeds, potentially making it difficult to meet future development needs. Consequently, there is an urgent need to develop new non-volatile memory devices to replace Flash and gain a mainstream market share, meeting the demand for high read / write speeds, high storage density, and low power consumption. Among the many new non-volatile memory devices, PCM, FeRAM, and MRAM face CMOS process compatibility issues, making them difficult to meet the requirements of ultra-large-scale integrated production. CBRAM devices, which use resistive switching to store data, have garnered widespread attention in academia and industry due to their minimal scaling effects, high storage density, compatibility with CMOS front-end and back-end processes, fast operation speed, and low power consumption. They hold great potential as the next generation of non-volatile memory devices. However, traditional CBRAM still faces significant challenges. For example, significant performance fluctuations, poor endurance, and poor consistency and retention characteristics remain to be addressed.

[0003] Currently, traditional pure metal electrode-based CBRAM devices still face significant challenges, hindering their large-scale integration and commercialization. Specifically, traditional CBRAM devices struggle to achieve ultra-low operating voltages. Typically, the forming voltage is high (>5V), the set voltage is greater than 3V, and the absolute value of the reset voltage is greater than 3V. Secondly, the consistency of the device's high and low resistance states and the set / reset transition voltages is poor, hindering precise control. Furthermore, poor stability during multiple cycle tests hinders multiple data read and write operations. The low ratio of high and low resistance values ​​hinders data storage.

[0004] Based on the shortcomings of the current pure metal electrode-based CBRAM devices, it is necessary to improve them. Summary of the Invention

[0005] In view of the above shortcomings or improvement needs of the prior art, the present invention provides an Ag-Cu electrode-based conductive bridge random access memory device and a preparation method thereof, so as to solve or at least partially solve the shortcomings of the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an Ag-Cu electrode-based conductive bridge random access memory device, comprising:

[0008] substrate;

[0009] a first electrode, which is located on the surface of the substrate;

[0010] a resistive switching layer, located on a surface of the first electrode away from the substrate;

[0011] Second electrodes, whose array is arranged on the surface of the resistive layer away from the substrate;

[0012] Wherein, the materials of the first electrode and the second electrode are active electrode materials or inert electrode materials. When the material of the first electrode is an active electrode material, the material of the second electrode is an inert electrode material; when the material of the first electrode is an inert electrode material, the material of the second electrode is an active electrode material;

[0013] The active electrode material is Ag-Cu alloy;

[0014] The material of the resistive layer includes any one of germanium telluride, selenium germanium, silicon oxide, tantalum oxide, hafnium oxide, and zirconium oxide.

[0015] Preferably, the inert electrode material includes at least one of Pt, Ti, Au, W, and TiN.

[0016] Preferably, the substrate includes any one of a Si substrate, a SiO2 substrate, a c-plane sapphire substrate, a magnesium oxide substrate, a gallium oxide substrate, a gallium nitride substrate, an NSTO substrate, a quartz glass substrate, an r-plane sapphire substrate, and an a-plane sapphire substrate.

[0017] Preferably, the second electrode is in a square or circle shape, the side length of the square is 10 nm to 10 mm, and the radius of the circle is 0.05 nm to 5 mm.

[0018] Preferably, the thickness of the first electrode is 1-800 nm;

[0019] The thickness of the resistive switching layer is 1-900 nm;

[0020] The thickness of the second electrode is 1-800 nm.

[0021] Preferably, the mass fraction of Cu in the Ag-Cu alloy is 7-90%, and the rest is Ag.

[0022] In a second aspect, the present invention further provides a method for preparing the Ag-Cu electrode-based conductive bridge random access memory device, comprising the following steps:

[0023] Prepare a first electrode on the surface of the substrate;

[0024] A resistive switching layer is prepared on the surface of the first electrode;

[0025] An array of second electrodes is prepared on the surface of the resistive switching layer.

[0026] Preferably, the preparation method of the Ag-Cu alloy comprises:

[0027] Ag-Cu alloy was prepared by magnetron sputtering using Ag target and Cu target as raw materials, respectively. The process parameters controlled during magnetron sputtering are: sputtering chamber pressure of 0.2~0.9Pa, sputtering power of Ag of 3~70W, sputtering time of Ag of 1~60min, sputtering power of Cu of 3~70W, and sputtering time of Cu of 1~60min.

[0028] Preferably, the resistive switching layer is prepared by magnetron sputtering, wherein the process parameters controlled during magnetron sputtering are: sputtering chamber pressure of 0.2-0.9 Pa, sputtering power of 5-100 W, and sputtering time of 5-80 min.

[0029] Preferably, a mask is used and magnetron sputtering is used to obtain the second electrode arranged in an array, wherein the process parameters controlled during magnetron sputtering are: the pressure of the sputtering chamber is 0.2~0.9Pa, the sputtering power is 3~70W, and the sputtering time is 1~60min.

[0030] The Ag-Cu electrode-based conductive bridge random access memory device and its preparation method of the present invention have the following advantages over the prior art:

[0031] 1. The Ag-Cu electrode-based conductive bridge random access memory device of the present invention utilizes Ag-Cu alloy electrodes instead of traditional pure metal electrodes, significantly improving device performance. This includes increasing the ratio of high and low resistance values, significantly reducing the forming voltage and set / reset transition voltage, and enhancing the consistency and stability of high and low resistance states and the set / reset transition voltage. This is achieved by optimizing the microstructure of the conductive filaments within the device, changing their morphology, and reducing the randomness of their growth, thereby optimizing the consistency and stability of the CBRAM device and effectively reducing operating power consumption. This invention promotes the development and large-scale commercialization of a new generation of low-power non-volatile memory devices.

[0032] 2. The Ag-Cu electrode-based conductive bridge random access memory device of the present invention has a lower operating voltage, wherein the forming voltage is about 4.1V, the average set voltage is about 0.32V, and the average reset voltage is about -0.28V. In addition, the increase in the memory window usually leads to a decrease in consistency and stability. However, the present invention effectively improves the balance between the two. The device of the present invention maintains low power consumption and high consistency in 100 read and write cycle tests, and the average memory window size reaches 5×10 3 It is obvious that the Ag-Cu electrode GeTe-based CBRAM device of the present invention has a significant improvement in performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort.

[0034] Figure 1 Schematic diagram of the structure of the Ag-Cu electrode-based conductive bridge random access memory device of the present invention;

[0035] Figure 2 This is the XPS analysis chart of the Ag element in the Ag-Cu alloy electrode prepared in Example 1;

[0036] Figure 3 This is the XPS analysis chart of the Cu element in the Ag-Cu alloy electrode prepared in Example 1;

[0037] Figure 4 1 is a comparison diagram of the forming curves of the CBRAM devices prepared in Example 1 and Comparative Example 1;

[0038] Figure 5 is an IV diagram of the Cu electrode-based conductive bridge random access memory device prepared in Comparative Example 1;

[0039] Figure 6 1 is an IV diagram of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1;

[0040] Figure 7 A comparison diagram of resistance state distributions of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1 and the Cu electrode-based conductive bridge random access memory device prepared in Comparative Example 1;

[0041] Figure 8This is a forming diagram of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2;

[0042] Figure 9 is an IV diagram of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2;

[0043] Figure 10 2 is a resistance state distribution diagram of the Ag electrode-based conductive bridge random access memory device prepared in comparative example 2;

[0044] Figure 11 This is a forming diagram of the Cu-Ag electrode-based conductive bridge random access memory device prepared in Example 2;

[0045] Figure 12 1 is an IV diagram of the Ag electrode-based conductive bridge random access memory device prepared in Example 2;

[0046] Figure 13 The resistance values ​​of the Ag-Cu electrode-based conductive bridge random access memory device in a high resistance state (HRS) and a low resistance state (LRS) prepared in Example 2 are read at a voltage of -0.051 V to obtain a resistance state distribution diagram of the device;

[0047] Figure 14 This is a forming diagram of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 3;

[0048] Figure 15 3 is an IV diagram of the Ag electrode-based conductive bridge random access memory device prepared in Example 3;

[0049] Figure 16 The resistance values ​​of the high resistance state (HRS) and low resistance state (LRS) of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 3 were read at a voltage of -0.051 V to obtain a resistance state distribution diagram of the device. DETAILED DESCRIPTION

[0050] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0051] In the description of the present invention, it should be understood that the directions or positions indicated by “upper” and the like are based on the directions or positions shown in the accompanying drawings, or are the directions or positions in which the product of the invention is usually placed when in use, or are the directions or positions commonly understood by those skilled in the art. These directions or positions are only for the convenience of describing the present invention and simplifying the description, and are not intended to indicate or imply that the device or component referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present invention.

[0052] The order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of this application, the term "including" means "including but not limited to". Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be understood as a rigid limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0053] The embodiment of the present application provides an Ag-Cu electrode-based conductive bridge random access memory device, such as Figure 1 Shown, including:

[0054] Substrate 1;

[0055] A first electrode 2, which is located on the surface of the substrate 1;

[0056] a resistive switching layer 3 , which is located on a surface of the first electrode 2 away from the substrate 1 ;

[0057] The second electrodes 4 are arranged in an array on the surface of the resistive layer 3 away from the substrate 1;

[0058] The materials of the first electrode 2 and the second electrode 4 are active electrode materials or inert electrode materials. When the material of the first electrode 2 is an active electrode material, the material of the second electrode 4 is an inert electrode material; when the material of the first electrode 2 is an inert electrode material, the material of the second electrode 4 is an active electrode material.

[0059] The active electrode material is Ag-Cu alloy;

[0060] The material of the resistive layer 3 is any one of germanium telluride (GeTe), germanium selenide (GeSe), silicon oxide (SiO 2 ), tantalum oxide (TaO x ), hafnium oxide (HfO x ), and zirconium oxide (ZrO 2 ).

[0061] The Ag-Cu electrode-based conductive bridge random access memory device of the present invention comprises a substrate 1, a first electrode 2, a resistive switching layer 3, and a second electrode 4; wherein the substrate 1, the first electrode 2, and the resistive switching layer 3 are stacked in sequence; the second electrode 4 is arranged in an array on the surface of the resistive switching layer 3 away from the substrate 1; the positions of the first electrode 2 and the second electrode 4 can be interchangeable, and the materials of the first electrode 2 and the second electrode 4 are active electrode materials or inert electrode materials. When the material of the first electrode 2 is the active electrode material, the material of the second electrode 4 is the inert electrode material; when the material of the first electrode 2 is the inert electrode material, the material of the second electrode 4 is the active electrode material; that is, when the first electrode 2 is the inert electrode material, the material of the second electrode 4 is the active electrode material; When electrode 2 is the active electrode, second electrode 4 is the inert electrode. When electrode 2 is the inert electrode, second electrode 4 becomes the active electrode. Specifically, germanium telluride (GeTe), germanium selenide (GeSe), silicon oxide (SiO2), and other materials are used as the resistive switching layer, while Ag-Cu alloy serves as the active electrode of the CBRAM. By replacing traditional pure metal electrodes with Ag-Cu alloy electrodes, the present invention significantly improves device performance, including increasing the ratio of high and low resistance values, significantly reducing the forming voltage and set / reset transition voltage, and enhancing the consistency and stability of the high and low resistance states and the set / reset transition voltage. This principle is based on optimizing the microstructure of the conductive filaments within the device, reducing the randomness of the filament growth, thereby improving the consistency and stability of the CBRAM device and effectively reducing operating power consumption. This invention promotes the development and large-scale commercialization of a new generation of low-power non-volatile memory devices.

[0062] Specifically, traditional pure metal electrode-based CBRAM devices still face significant challenges, hindering large-scale commercial integration. Specifically, traditional CBRAM devices struggle to achieve ultra-low operating voltages. Typically, they have a high forming voltage (>5V), a set voltage greater than 3V, and a reset voltage greater than 3V. Secondly, the consistency between the device's high and low resistance states and the set / reset transition voltages is poor, hindering precise control. Furthermore, their stability during multiple cycle tests is poor, hindering multiple data read and write operations. The low ratio of high and low resistance values ​​hinders data storage. The GeTe-based CBRAM device with Ag-Cu electrodes in this invention offers the advantages of simple fabrication, low cost, and compatibility with modern CMOS processes. Most importantly, the Ag-Cu electrode-based conductive bridge random access memory device in this invention achieves a reduced operating voltage, with a forming voltage of approximately 4.1V, an average set voltage of approximately 0.32V, and an average reset voltage of approximately -0.28V. In addition, the increase of storage window usually leads to the decrease of consistency and stability. However, the present invention effectively improves the balance between the two. The device of the present invention maintains low power consumption and high consistency in 100 read and write cycle tests, and the average storage window size reaches 5×10 3 It is obvious that the Ag-Cu electrode GeTe-based CBRAM device of the present invention has a significant improvement in performance optimization.

[0063] In some embodiments, the inert electrode material includes at least one of Pt, Ti, Au, W, and TiN.

[0064] In some embodiments, the substrate 1 includes any one of a Si substrate, a SiO2 substrate, a c-plane sapphire substrate, a magnesium oxide substrate, a gallium oxide substrate, a gallium nitride substrate, an NSTO substrate, a quartz glass substrate, an r-plane sapphire substrate, and an a-plane sapphire substrate.

[0065] In some embodiments, the second electrode 4 is in a square or circle shape, the side length of the square is 10 nm to 10 mm, and the diameter of the circle is 0.1 to 10 mm.

[0066] In some embodiments, the thickness of the first electrode 2 is 1-800 nm.

[0067] In some embodiments, the thickness of the resistive switching layer 3 is 1-900 nm.

[0068] In some embodiments, the thickness of the second electrode 4 is 1-800 nm.

[0069] In some embodiments, the thickness of the substrate 1 is 1-10 μm.

[0070] In some embodiments, the mass fraction of Cu in the Ag-Cu alloy is 7-90%, and the remainder is Ag (i.e., the mass fraction of Ag is 93-10%);

[0071] In some embodiments, the material of the resistive layer 3 includes any one of germanium telluride (GeTe), germanium selenide (GeSe), silicon oxide (SiO2), tantalum oxide (TaOx), hafnium oxide (HfOx), and zirconium oxide (ZrO2);

[0072] Furthermore, the Ag-Cu electrode-based conductive bridge random access memory device of the present invention comprises a three-layer structure: a first electrode, a resistive switching layer, and a second electrode. The first electrode or the second electrode is composed of an Ag-Cu alloy and deposited on a substrate. As shown in Figure 1, the resistive switching layer is composed of any one of germanium telluride (GeTe), germanium selenide (GeSe), silicon oxide (SiO2), tantalum oxide (TaOx), hafnium oxide (HfOx), or zirconium oxide (ZrO2), and the inert electrode material is composed of at least one of Pt, Ti, Au, and Cu. The second electrode is square or circular in shape, with a side length of 10 nm to 10 mm and a radius of 0.05 nm to 5 mm. The basic resistive switching function of CBRAM is achieved by applying an external voltage between the first and second electrodes. Specifically, the active electrode material, an Ag-Cu alloy, and the inert electrode material are connected to external signal excitation at both ends, forming a current loop. By regulating the external voltage, limiting the current, and pulse signal, the CBRAM switches between high-resistance and low-resistance states when the resistance change conditions are met, thereby completing the storage of information data. Furthermore, the external excitation can simulate the relevant characteristics of biological synapses, promoting the application of neuromorphic computing.

[0073] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned Ag-Cu electrode-based conductive bridge random access memory device, comprising the following steps:

[0074] S1, preparing a first electrode on the surface of the substrate;

[0075] S2, preparing a resistive switching layer on the surface of the first electrode;

[0076] S3. Prepare a second electrode array on the surface of the resistive switching layer.

[0077] In some embodiments, the active electrode material is Ag-Cu alloy, and the preparation method of the Ag-Cu alloy is: the active electrode is prepared by magnetron sputtering using Ag target and Cu target as raw materials, respectively, wherein the process parameters controlled during magnetron sputtering are: the pressure of the sputtering chamber is 0.2~0.9Pa, the sputtering power of Ag is 3~70W, the sputtering time of Ag is 1~60min, the sputtering power of Cu is 3~70W, and the sputtering time of Cu is 1~60min.

[0078] In some embodiments, the resistive switching layer is prepared by magnetron sputtering, wherein the process parameters controlled during magnetron sputtering are: sputtering chamber pressure of 0.2~0.9Pa, sputtering power of 5~100W, and sputtering time of 5~80min.

[0079] In some embodiments, a mask is used and magnetron sputtering is used to prepare an array of second electrodes on the surface of the resistive layer, wherein the process parameters controlled during magnetron sputtering are: the pressure of the sputtering chamber is 0.2~0.9Pa, the sputtering power is 3~70W, and the sputtering time is 1~60min.

[0080] In some embodiments, before preparing the first electrode on the surface of the substrate, the substrate is also cleaned; specifically, the cleaning method is: first, the substrate substrate is placed in a beaker, and acetone is poured in for cleaning. Since acetone is a volatile solution, it needs to be sealed with plastic wrap, and then ultrasonically cleaned for 30 to 35 minutes. This step is mainly to remove impurities such as organic matter; after cleaning, the substrate is taken out with tweezers, and then placed in another beaker, and anhydrous ethanol is poured in, and ultrasonic cleaning is performed for 20 to 30 minutes. This step mainly removes acetone and other surface contaminants; finally, the substrate is placed in a beaker filled with deionized water and ultrasonically cleaned for 10 to 20 minutes. After the ultrasonic cleaning is completed, it is blown dry for use.

[0081] In some embodiments, the material of the first electrode is an Ag-Cu alloy, and the first electrode is prepared on the surface of the substrate, specifically comprising: first, mounting a metal Cu target and a metal Ag target on a DC sputtering target holder of a magnetron sputtering device, turning on a molecular pump and a mechanical pump to pump air until the pressure in the sputtering vacuum chamber is less than 2×10 -4 Pa; turn on the argon gas and circulating cooling water. Then stick insulating tape on one edge of the cleaned substrate, fix it on the sample tray in the magnetron sputtering equipment, put it into the small chamber, and wait until the pressure in the small chamber reaches 5×10 -3Pa, transfer the Si substrate to a vacuum sputtering chamber; the present invention utilizes co-sputtering to prepare Ag-Cu alloy electrodes. By regulating the sputtering temperature, sputtering pressure, sputtering power, sputtering time, and argon gas flow rate, high-performance CBRAM devices can be fabricated. Specifically, at room temperature (25°C), the argon gas flow rate is controlled between 50 and 60 sccm, the sputtering chamber pressure is between 0.2 and 0.9 Pa, the sputtering power for Ag is between 3 and 70 W, the sputtering time for Ag is between 1 and 60 minutes, and the sputtering power for Cu is between 3 and 70 W, and the sputtering time for Cu is between 1 and 60 minutes. After adjusting the process parameters as described above, turn on the DC power supply, enter the process parameters, check the operating status, and begin co-sputtering of Ag and Cu. The sputtering process is then continued according to the set process parameters. After the sputtering deposition is completed, the system pressure in the small chamber is restored to atmospheric pressure, the substrate is removed from the magnetron sputtering instrument, and the DC power supply and the argon circulating cooling water switches are turned off to obtain the Ag-Cu alloy electrode film.

[0082] In some embodiments, a resistive switching layer film (such as a GeTe film) is prepared by removing the substrate with the Ag-Cu alloy electrode film, retaining the insulating adhesive attached to the substrate, and then covering it with a larger layer of insulating adhesive, leaving the Ag-Cu film area for electrical testing and analysis. The sample is then placed in the sputtering chamber of a magnetron sputtering device, following the same procedures as described above for preparing the Ag-Cu alloy. It is worth noting that the resistive switching layer film preparation only requires turning on the corresponding RF target switch, controlling the argon flow rate at 50-60 sccm at room temperature (25°C), the sputtering chamber pressure at 0.2-0.9 Pa, the sputtering power at 5-100 W, and the sputtering time at 5-80 minutes. After adjusting the process parameters as described above, turn on the RF power switch, enter the process parameters, check the operating status, and start sputtering. The sputtering process is then repeated according to the set process parameters. After sputtering deposition is complete, the system pressure in the chamber is returned to atmospheric pressure, the substrate is removed from the magnetron sputtering device, and the RF power and argon circulating cooling water are turned off to obtain the resistive switching layer film.

[0083] In some embodiments, the second electrode is made of an inert electrode material (such as Ti). An array of second electrodes is fabricated on the surface of the resistive switching layer. Specifically, after removing the substrate with the resistive switching layer film, retain the insulating adhesive attached to the substrate. A mask is placed over one side of the resistive switching layer and secured with the insulating adhesive. The mask apertures are either square or circular, with a square side length of 0.1 mm to 1 mm and a circular radius of 0.05 to 0.5 mm. Therefore, the size and shape of the fabricated Ti electrodes match the mask. The tray with the mask is placed in a small chamber, and the resistive switching layer fabrication steps are repeated, except that the power switch is replaced with a DC sputtering power switch corresponding to the inert electrode material target. However, it should be noted that the fabrication process parameters are not identical. Specifically, at room temperature (25°C), the argon flow rate is controlled at 40-50 sccm, the sputtering chamber pressure is 0.2-0.9 Pa, the sputtering power is 3-70 W, and the sputtering time is 1-60 minutes. After sputtering, the sample is taken out and the insulating glue is removed to obtain a circular or square Ag-Cu alloy electrode-based CBRAM device.

[0084] The following further illustrates the Ag-Cu electrode-based conductive bridge random access memory device and its preparation method of the present application with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be understood as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0085] Example 1

[0086] An embodiment of the present application provides an Ag-Cu electrode-based conductive bridge random access memory device, comprising:

[0087] substrate;

[0088] a first electrode located on the surface of the substrate;

[0089] a resistive switching layer, which is located on a surface of the first electrode away from the substrate;

[0090] The second electrodes are arranged in an array on a surface of the resistive layer away from the substrate;

[0091] Wherein, the material of the first electrode is an active electrode material, and the material of the active electrode is an Ag-Cu alloy;

[0092] The second electrode is made of an inert electrode material, and the inert electrode material is Ti;

[0093] The material of the resistive switching layer is GeTe;

[0094] The substrate is a Si substrate;

[0095] The second electrode is in the shape of a square, and the side length of the square is 5 mm;

[0096] The thickness of the first electrode is 150 nm;

[0097] The thickness of the resistive switching layer is 180nm;

[0098] The thickness of the second electrode is 100 nm; the thickness of the substrate is 10 μm;

[0099] The mass fraction of Ag in the Ag-Cu alloy is 60%; the mass fraction of Cu is 40%.

[0100] The method for preparing the Ag-Cu electrode-based conductive bridge random access memory device in the above-mentioned embodiment 1 comprises the following steps:

[0101] S1. The Si substrate was ultrasonically cleaned with acetone for 30 min, anhydrous ethanol for 20 min, and deionized water for 10 min, and then dried for later use.

[0102] S2. Ag-Cu alloy was prepared on the cleaned Si substrate by magnetron sputtering using Ag target and Cu target as raw materials, i.e., the first electrode. The process parameters controlled during magnetron sputtering were: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of Ag of 20 W, sputtering time of Ag of 30 min, sputtering power of Cu of 10 W, and sputtering time of Cu of 30 min.

[0103] S3. Using a GeTe target as a raw material, a GeTe resistive switching layer is prepared on the first electrode by magnetron sputtering. The process parameters controlled during the magnetron sputtering are: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of 40 W, and sputtering time of 40 min.

[0104] S4. Using Ti target as raw material, a mask plate and magnetron sputtering method are used to prepare the second electrode of array arrangement on the surface of the resistive layer; wherein, the process parameters controlled during magnetron sputtering are: temperature is room temperature 25°C, argon flow rate is 40sccm, sputtering chamber pressure is 0.3Pa, sputtering power is 20W, and sputtering time is 40min.

[0105] Example 2

[0106] An embodiment of the present application provides an Ag-Cu electrode-based conductive bridge random access memory device, comprising:

[0107] substrate;

[0108] a first electrode located on the surface of the substrate;

[0109] a resistive switching layer, which is located on a surface of the first electrode away from the substrate;

[0110] The second electrodes are arranged in an array on a surface of the resistive layer away from the substrate;

[0111] Wherein, the material of the first electrode is an active electrode material, and the material of the active electrode is an Ag-Cu alloy;

[0112] The second electrode is made of an inert electrode material, and the inert electrode material is Ti;

[0113] The material of the resistive switching layer is GeTe;

[0114] The substrate is a Si substrate;

[0115] The second electrode is in the shape of a square, and the side length of the square is 5 mm;

[0116] The thickness of the first electrode is 200 nm;

[0117] The thickness of the resistive switching layer is 180nm;

[0118] The thickness of the second electrode is 100 nm; the thickness of the substrate is 10 μm;

[0119] The mass fraction of Ag in the Ag-Cu alloy is 10%; the mass fraction of Cu is 90%.

[0120] The method for preparing the Ag-Cu electrode-based conductive bridge random access memory device in the above-mentioned embodiment 2 comprises the following steps:

[0121] S1. The Si substrate was ultrasonically cleaned with acetone for 30 min, anhydrous ethanol for 20 min, and deionized water for 10 min, and then dried for later use.

[0122] S2. Using Ag and Cu targets as raw materials, respectively, a Ag-Cu alloy was prepared on a cleaned Si substrate by magnetron sputtering, i.e., the first electrode. The process parameters controlled during magnetron sputtering were: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of Ag of 3 W, sputtering time of Ag of 30 min, sputtering power of Cu of 40 W, and sputtering time of Cu of 30 min.

[0123] S3. Using a GeTe target as a raw material, a GeTe resistive switching layer is prepared on the first electrode by magnetron sputtering. The process parameters controlled during the magnetron sputtering are: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of 40 W, and sputtering time of 40 min.

[0124] S4. Using Ti target as raw material, a mask plate and magnetron sputtering method are used to prepare the second electrode of array arrangement on the surface of the resistive layer; wherein, the process parameters controlled during magnetron sputtering are: temperature is room temperature 25°C, argon flow rate is 40sccm, sputtering chamber pressure is 0.3Pa, sputtering power is 20W, and sputtering time is 40min.

[0125] Example 3

[0126] An embodiment of the present application provides an Ag-Cu electrode-based conductive bridge random access memory device, comprising:

[0127] substrate;

[0128] a first electrode located on the surface of the substrate;

[0129] a resistive switching layer, which is located on a surface of the first electrode away from the substrate;

[0130] The second electrodes are arranged in an array on a surface of the resistive layer away from the substrate;

[0131] Wherein, the material of the first electrode is an active electrode material, and the material of the active electrode is an Ag-Cu alloy;

[0132] The second electrode is made of an inert electrode material, and the inert electrode material is Ti;

[0133] The material of the resistive switching layer is GeTe;

[0134] The substrate is a Si substrate;

[0135] The second electrode is in the shape of a square, and the side length of the square is 5 mm;

[0136] The thickness of the first electrode is 200 nm;

[0137] The thickness of the resistive switching layer is 180nm;

[0138] The thickness of the second electrode is 100 nm; the thickness of the substrate is 10 μm;

[0139] The mass fraction of Ag in the Ag-Cu alloy is 93%; the mass fraction of Cu is 7%.

[0140] The method for preparing the Ag-Cu electrode-based conductive bridge random access memory device in the above-mentioned embodiment 3 comprises the following steps:

[0141] S1. The Si substrate was ultrasonically cleaned with acetone for 30 min, anhydrous ethanol for 20 min, and deionized water for 10 min, and then dried for later use.

[0142] S2. Using Ag and Cu targets as raw materials, respectively, a Ag-Cu alloy was prepared on a cleaned Si substrate by magnetron sputtering, i.e., the first electrode. The process parameters controlled during magnetron sputtering were: room temperature 25°C, argon flow rate 50 sccm, sputtering chamber pressure 0.35 Pa, Ag sputtering power 40 W, Ag sputtering time 30 min, Cu sputtering power 3 W, and Cu sputtering time 30 min.

[0143] S3. Using a GeTe target as a raw material, a GeTe resistive switching layer is prepared on the first electrode by magnetron sputtering. The process parameters controlled during the magnetron sputtering are: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of 40 W, and sputtering time of 40 min.

[0144] S4. Using Ti target as raw material, a mask plate and magnetron sputtering method are used to prepare the second electrode of array arrangement on the surface of the resistive layer; wherein, the process parameters controlled during magnetron sputtering are: temperature is room temperature 25°C, argon flow rate is 40sccm, sputtering chamber pressure is 0.3Pa, sputtering power is 20W, and sputtering time is 40min.

[0145] Comparative Example 1

[0146] This comparative example 1 provides a method for preparing a Cu electrode-based conductive bridge random access memory device, which is similar to that of Example 1, except that in step S2, the sputtering power of Ag is 0 W and the sputtering power of Cu is 10 W. The method specifically includes the following steps:

[0147] S1. The Si substrate was ultrasonically cleaned with acetone for 30 min, anhydrous ethanol for 20 min, and deionized water for 10 min, and then dried for later use.

[0148] S2. Ag-Cu alloy was prepared on the cleaned Si substrate by magnetron sputtering using Ag target and Cu target as raw materials, i.e., the first electrode. The process parameters controlled during magnetron sputtering were: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of Ag of 0 W, sputtering time of Ag of 30 min, sputtering power of Cu of 10 W, and sputtering time of Cu of 30 min.

[0149] S3. Using a GeTe target as a raw material, a GeTe resistive switching layer is prepared on the first electrode by magnetron sputtering. The process parameters controlled during the magnetron sputtering are: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of 40 W, and sputtering time of 40 min.

[0150] S4. Using Ti target as raw material, a mask plate and magnetron sputtering method are used to prepare the second electrode of array arrangement on the surface of the resistive layer; wherein, the process parameters controlled during magnetron sputtering are: temperature is room temperature 25°C, argon flow rate is 40sccm, sputtering chamber pressure is 0.3Pa, sputtering power is 20W, and sputtering time is 40min.

[0151] Comparative Example 2

[0152] Comparative Example 2 provides a method for preparing an Ag electrode-based conductive bridge random access memory device, which is similar to Example 1 except that the sputtering power of Ag in step S2 is 20 W and the sputtering power of Cu is 0 W. The method specifically includes the following steps:

[0153] S1. The Si substrate was ultrasonically cleaned with acetone for 30 min, anhydrous ethanol for 20 min, and deionized water for 10 min, and then dried for later use.

[0154] S2. Ag-Cu alloy was prepared on the cleaned Si substrate by magnetron sputtering using Ag target and Cu target as raw materials, i.e., the first electrode. The process parameters controlled during magnetron sputtering were: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of Ag of 20 W, sputtering time of Ag of 30 min, sputtering power of Cu of 0 W, and sputtering time of Cu of 30 min.

[0155] S3. Using a GeTe target as a raw material, a GeTe resistive switching layer is prepared on the first electrode by magnetron sputtering. The process parameters controlled during the magnetron sputtering are: temperature of room temperature 25°C, argon flow rate of 50 sccm, sputtering chamber pressure of 0.35 Pa, sputtering power of 40 W, and sputtering time of 40 min.

[0156] S4. Using Ti target as raw material, a mask plate and magnetron sputtering method are used to prepare the second electrode of array arrangement on the surface of the resistive layer; wherein, the process parameters controlled during magnetron sputtering are: temperature is room temperature 25°C, argon flow rate is 40sccm, sputtering chamber pressure is 0.3Pa, sputtering power is 20W, and sputtering time is 40min.

[0157] Performance Testing

[0158] The CBRAM devices prepared in Example 1 and Comparative Examples 1-2 were subjected to corresponding performance tests, and all the tests were performed on an Agilent B1500A semiconductor parameter analyzer test platform.

[0159] Figure 2This is the XPS analysis diagram of the Ag element in the Ag-Cu alloy electrode prepared in Example 1.

[0160] Figure 3 This is the XPS analysis chart of the Cu element in the Ag-Cu alloy electrode prepared in Example 1.

[0161] from Figure 2 It can be seen that the XP image of the Ag element in the Ag-Cu alloy electrode has two obvious peaks, corresponding to different binding energies, representing the two hybrid orbitals of the Ag element, and mainly presents the zero-valent elemental Ag, proving that the Ag atom has not been oxidized to Ag. + .according to Figure 3 It is known that the XPS image of Cu element has multiple peaks, showing a variety of chemical states, including single substance Cu and Cu 2+ , proving that part of Cu was oxidized to Cu 2+ According to Figures 2 and 3, Ag promotes the oxidation of Cu, forming more Cu 2+ Being reduced to Cu promotes the growth of Cu conductive filaments in Ag-Cu electrode-based devices, forming more stable Cu conductive filaments, which is beneficial to improving the electrical performance of GeTe-based CBRAM devices.

[0162] Figure 4 1 is a comparison diagram of the forming curves of the CBRAM devices prepared in Example 1 and Comparative Example 1; Figure 4 Cu represents the forming curve of the Cu electrode-based conductive bridge random access memory device prepared in Comparative Example 1, and Ag-Cu represents the forming curve of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1.

[0163] Specifically, the resistive IV characteristics of the CBRAM devices prepared in Example 1 and Comparative Example 1 were tested. The CBRAM devices prepared in Example 1 and Comparative Example 1 were placed on the probe station of an Agilent B1500A semiconductor parameter analyzer. A positive probe was placed in close contact with the Ag-Cu electrode (i.e., the first electrode) of the CBRAM device (Comparative Example 1 used a pure Cu electrode). Similarly, a negative probe was placed in close contact with the Ti electrode (i.e., the second electrode). A DC voltage of 0 to 8 V was applied to the Ti electrode to perform the forming process. As shown in Figure 4, when the voltage was approximately 6 V, the resistance state of the CBRAM device with a pure Cu electrode in Comparative Example 1 changed from an initial high-resistance state to a low-resistance state. This voltage is the forming voltage. The forming voltage of the Ag-Cu alloy-based device in Example 1 was approximately 4.1 V, demonstrating that the Ag-Cu alloy electrode has the effect of reducing the forming voltage.

[0164] Figure 5 This is an IV diagram of the Cu electrode-based conductive bridge random access memory device prepared in Comparative Example 1.

[0165] Figure 6 This is the IV diagram of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1.

[0166] Specifically, a bidirectional scanning voltage cycle IV test was performed on the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1. The IV curve obtained after 100 scanning voltage cycle tests is shown in FIG6 .

[0167] Figure 6 The IV curve exhibits distinct bipolar resistance transition characteristics. A sweep voltage cycle consists of four steps: first, from 0 V to 0.6 V, then from 0.6 V to 0 V, then from 0 V to -0.6 V, and finally from -0.6 V to 0 V. Each sweep cycle consists of 101 steps. To prevent device breakdown caused by excessive current during testing, a 100 μA current limit is set during the set phase. When the voltage reaches approximately 0.32 V, the device current suddenly increases, transitioning from a high-resistance state to a low-resistance state. This process is known as the set phase. When the voltage reaches approximately -0.28 V, the current suddenly decreases, transitioning from a low-resistance state back to a high-resistance state. This is known as the reset phase. Switching the device's resistance state by controlling an external stimulus enables data storage. The low-resistance state of the CBRAM device corresponds to a digital signal "0," while the high-resistance state corresponds to a digital signal "1." Multiple sweep cycles demonstrate the device's non-volatile nature and excellent retention. In a similar manner, appropriate set / reset voltage, current limit and other parameters are adjusted to test the IV characteristic curve of the CBRAM of the pure Cu electrode device obtained in comparative embodiment 1, as shown in FIG5 . Figure 5 The set / reset voltage (0.45 / -0.50V) of the Cu electrode-based conductive bridge random access memory device prepared in Example 1 is significantly higher than the set / reset voltage (0.3 / -0.28V) of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1. In addition, the stability and consistency of the pure Cu-based CBRAM device are worse than those of the Ag-Cu alloy electrode-based device.

[0168] The resistance values ​​of the high resistance state (HRS) and low resistance state (LRS) of the CBRAM devices obtained in Example 1 and Comparative Example 1 were read at a voltage of -0.051 V to obtain resistance state distribution diagrams of the devices with the two material structures, as shown in FIG7 .

[0169] Figure 7 Cu represents the Cu electrode-based conductive bridge random access memory device prepared in Comparative Example 1, and Ag—Cu represents the Ag—Cu electrode-based conductive bridge random access memory device prepared in Example 1.

[0170] from Figure 7 It can be seen that the storage window of the Ag-Cu electrode-based conductive bridge random access memory device in Example 1 reaches an average of 5×10 3 The above values ​​are much greater than those of the Cu electrode-based conductive bridge random access memory device prepared in Comparative Example 1, and the consistency is significantly improved. Experiments have shown that it can be used as a good non-volatile memory device.

[0171] Figure 8 This is a forming diagram of the Ag electrode-based conductive bridge random access memory device prepared in comparative example 2.

[0172] from Figure 8 It can be seen that the forming voltage of the GeTe-based CBRAM device with Ag electrode prepared in comparative example 2 is about 6.2V, which is greater than that of the Cu electrode-based conductive bridge random access memory device prepared in comparative example 1 and greater than that of the Ag-Cu electrode-based conductive bridge random access memory device prepared in example 1; this further proves that the use of Ag-Cu alloy electrodes is an effective method to reduce the forming voltage.

[0173] Figure 9 2 is an IV diagram of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2.

[0174] from Figure 9 It can be seen that the consistency and window size of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2 are inferior to those of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1. In addition, the average set / reset voltage of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2 is 0.85 / -0.75V, respectively, which is significantly greater than the average set / reset voltage (0.3 / -0.28V) of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 1, indicating that the Ag-Cu electrode-based device can achieve lower power consumption.

[0175] Figure 10 The resistance values ​​of the high resistance state (HRS) and low resistance state (LRS) of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2 were read at a voltage of -0.051 V to obtain a resistance state distribution diagram of the device.

[0176] from Figure 10It can be seen that the high-to-low resistance state ratio of the Ag electrode-based conductive bridge random access memory device prepared in comparative example 2 is >10, but is smaller than that of the Ag-Cu electrode-based conductive bridge random access memory device prepared in example 1 (>5000), and has worse consistency.

[0177] Figure 11 Forming diagram of the Cu-Ag electrode (Ag mass fraction is 10%, Cu mass fraction is 90%) based conductive bridge random access memory device prepared in Example 2; Figure 11 It can be seen that its forming voltage is 5.2 V, which is lower than the voltage of the Cu electrode-based device prepared in Comparative Example 1 (6.2 V) and the voltage of the Ag electrode-based device prepared in Comparative Example 2 (6 V).

[0178] Figure 12 : This is the IV diagram of the Ag electrode-based conductive bridge random access memory device prepared in Example 2. Figure 12 It can be seen that the consistency and window size of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 2 are better than those of the conductive bridge random access memory devices prepared in Comparative Example 1 and Comparative Example 2.

[0179] Figure 13 The resistance values ​​of the high resistance state (HRS) and low resistance state (LRS) of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 2 were read at a voltage of -0.051 V to obtain a resistance state distribution diagram of the device.

[0180] from Figure 13 As can be seen from the data, the high-to-low resistance ratio of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 2 is greater than 20, which is greater than that of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2 (>10), and has better consistency. Furthermore, its durability is superior to that of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 1.

[0181] Figure 14 The forming diagram of the Ag-Cu electrode (mass fraction of Ag is 93%, mass fraction of Cu is 7%) based conductive bridge random access memory device prepared in Example 3; Figure 14 It can be seen that the forming voltage is 4.9 V, which is lower than the voltage of the Cu electrode-based device prepared in Comparative Example 1 (6.2 V) and the voltage of the Ag electrode-based device prepared in Comparative Example 2 (6 V).

[0182] Figure 15 : This is the IV diagram of the Ag electrode-based conductive bridge random access memory device prepared in Example 3. Figure 15It can be seen that the consistency and stability of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 3 are better than those of the conductive bridge random access memory devices prepared in Comparative Example 1 and Comparative Example 2.

[0183] Figure 16 The resistance values ​​of the high resistance state (HRS) and low resistance state (LRS) of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 3 were read at a voltage of -0.051 V to obtain a resistance state distribution diagram of the device.

[0184] from Figure 16 As can be seen from the graph, the high-to-low resistance ratio of the Ag-Cu electrode-based conductive bridge random access memory device prepared in Example 3 is greater than 10, and its consistency and stability are better than those of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 2, and its consistency is even better. In addition, its durability is better than that of the Ag electrode-based conductive bridge random access memory device prepared in Comparative Example 1.

[0185] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An Ag-Cu electrode-based conductive bridge random access memory device, characterized in that: include: substrate; a first electrode, which is located on the surface of the substrate; a resistive switching layer, located on a surface of the first electrode away from the substrate; Second electrodes, whose array is arranged on the surface of the resistive switching layer away from the substrate; Wherein, the materials of the first electrode and the second electrode are active electrode materials or inert electrode materials. When the material of the first electrode is an active electrode material, the material of the second electrode is an inert electrode material; when the material of the first electrode is an inert electrode material, the material of the second electrode is an active electrode material; The active electrode material is Ag-Cu alloy; The material of the resistive layer includes any one of germanium telluride, selenium germanium, silicon oxide, tantalum oxide, hafnium oxide, and zirconium oxide.

2. The Ag-Cu electrode-based conductive bridge random access memory device according to claim 1, wherein: The mass fraction of Cu in the Ag-Cu alloy is 7-90%, and the rest is Ag.

3. The Ag-Cu electrode-based conductive bridge random access memory device according to claim 1, wherein: The inert electrode material includes at least one of Pt, Ti, Au, W, and TiN.

4. The Ag-Cu electrode-based conductive bridge random access memory device according to claim 1, wherein: The substrate includes any one of a Si substrate, a SiO2 substrate, a c-plane sapphire substrate, a magnesium oxide substrate, a gallium oxide substrate, a gallium nitride substrate, an NSTO substrate, a quartz glass substrate, an r-plane sapphire substrate, and an a-plane sapphire substrate.

5. The Ag-Cu electrode-based conductive bridge random access memory device according to claim 1, wherein: The second electrode is in a square or circle shape, the side length of the square is 10 nm to 10 mm, and the radius of the circle is 0.05 nm to 5 mm.

6. The Ag-Cu electrode-based conductive bridge random access memory device according to claim 1, wherein: The thickness of the first electrode is 1-800 nm; The thickness of the resistive switching layer is 1-900 nm; The thickness of the second electrode is 1-800 nm.

7. A method for preparing a Ag-Cu electrode-based conductive bridge random access memory device according to any one of claims 1 to 6, characterized in that: The following steps are involved: Prepare a first electrode on the surface of the substrate; A resistive switching layer is prepared on the surface of the first electrode; An array of second electrodes is prepared on the surface of the resistive switching layer.

8. The method for preparing the Ag-Cu electrode-based conductive bridge random access memory device according to claim 7, wherein: The preparation method of the Ag-Cu alloy comprises: Ag-Cu alloy was prepared by magnetron sputtering using Ag target and Cu target as raw materials, respectively. The process parameters controlled during magnetron sputtering are: sputtering chamber pressure of 0.2~0.9Pa, sputtering power of Ag of 3~70W, sputtering time of Ag of 1~60min, sputtering power of Cu of 3~70W, and sputtering time of Cu of 1~60min.

9. The method for preparing the Ag-Cu electrode-based conductive bridge random access memory device according to claim 7, wherein: The resistive switching layer is prepared by magnetron sputtering, wherein the process parameters controlled during magnetron sputtering are: sputtering chamber pressure of 0.2~0.9Pa, sputtering power of 5~100W, and sputtering time of 5~80min.

10. The method for preparing the Ag-Cu electrode-based conductive bridge random access memory device according to claim 7, wherein: The second electrode of the array arrangement is obtained by using a mask and a magnetron sputtering method, wherein the process parameters controlled during the magnetron sputtering are: the pressure of the sputtering chamber is 0.2~0.9Pa, the sputtering power is 3~70W, and the sputtering time is 1~60min.